1995
DOI: 10.1080/01635589509514404
|View full text |Cite
|
Sign up to set email alerts
|

RRR‐α‐tocopheryl succinate inhibits the proliferation of human prostatic tumor cells with defective cell cycle/differentiation pathways

Abstract: The RRR-alpha-tocopheryl succinate derivative of vitamin E, referred to as vitamin E succinate (VES), inhibits the proliferation of three metastatic human prostatic cancer cell lines, LNCaP, PC-3, and DU-145. LNCaP is a lymph node-derived androgen-sensitive prostate cell line; these cells are defective for response to transforming growth factor-beta (TGF-beta) but are normal for cell cycle-related tumor suppressor genes: p53 and retinoblastoma (Rb). PC-3 is a bone marrow-derived androgen-insensitive prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Out of the eight different tocopherols included in the term vitamin E, a-tocopherol often exerts specific functions and is the predominant form of vitamin E found in plasma and tissues, whereas g-tocopherol, and not a-tocopherol, is the major form present in the diet. Besides its antioxidant function, vitamin E and its analogues can modulate transforming growth factor-h and AR/PSA signaling pathway and regulate cell cycle through DNA synthesis arrest in LNCaP, PC-3, and DU-145 CaP cells (21). Induction of apoptosis, by causing depletion of cytosolic Fas with increase in the membrane levels of Fas, decreased production of vascular endothelial growth factor, and inhibition of matrix metalloproteinases are other mechanisms through which vitamin E inhibits prostate carcinogenesis (22).…”
Section: Vitamin Ementioning
confidence: 99%
“…Out of the eight different tocopherols included in the term vitamin E, a-tocopherol often exerts specific functions and is the predominant form of vitamin E found in plasma and tissues, whereas g-tocopherol, and not a-tocopherol, is the major form present in the diet. Besides its antioxidant function, vitamin E and its analogues can modulate transforming growth factor-h and AR/PSA signaling pathway and regulate cell cycle through DNA synthesis arrest in LNCaP, PC-3, and DU-145 CaP cells (21). Induction of apoptosis, by causing depletion of cytosolic Fas with increase in the membrane levels of Fas, decreased production of vascular endothelial growth factor, and inhibition of matrix metalloproteinases are other mechanisms through which vitamin E inhibits prostate carcinogenesis (22).…”
Section: Vitamin Ementioning
confidence: 99%
“…It has been shown to inhibit the growth of several human cancer cell lines including prostate. 6 We have shown that vitamin E induces growth arrest in prostate cancer cell lines mediated by alterations in cell cycle regulatory proteins, particularly p27 Kipl . 7 We have extended our study to determine the interaction between vitamin E and selenium in prostate cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E succinate (VES) is the succinate derivative of a-tocopherol and has the most effective antitumorigenic activity in a variety of cell culture and animal models (3 -8). The antitumorigenic activity of VES includes inhibition of proliferation (9,10), invasion (11), and angiogenesis (12) and induction of apoptosis (13). VES induces apoptosis in many types of cancer cells, including breast, cervical, endometrial, colon, and prostate.…”
Section: Introductionmentioning
confidence: 99%